Nano soldering paste and preparation method

By using modified nanosilver-copper solder powder, surface modified nanoNi particles, esterified modified rosin and homemade mixed activator in solder paste, the problems of residual and welding quality after welding are solved, and the continuous uniform growth of solder joints and the reduction of residual after welding are achieved.

CN119566611AInactive Publication Date: 2025-03-07JIANGSU SANWAL ELECTRONIC SCI&TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510134746.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-07
Publication Date
2025-03-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing solder paste will cause post-welding residue during the welding process, affecting stability and welding quality, and miscellaneous elements may damage the soldered product.

Method used

A nanosolder paste was prepared by improving the nanostructure of solder powder, reducing surface tension, removing the influence of metal hetero ions and improving the activity of the activator.

Benefits of technology

The continuous and uniform growth of welding joints is achieved, the spreadability and expansion rate of welding joints is improved, the residual after welding is reduced, and the welding quality and product stability are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119566611A_ABST
    Figure CN119566611A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of soldering paste preparation, and particularly discloses nano soldering paste and a preparation method thereof.The nano soldering paste comprises modified nano silver-copper soldering powder, scaling powder and surface modified nano Ni particles; a preparation method of the modified nano-silver-copper solder powder comprises the steps that solder powder is added into a 0.01 M dilute nitric acid solution with the volume being 5 times of the weight of the solder powder, stirring is conducted for 5 min, a mixture aqueous solution containing 0.02 mol / L sodium hydroxide and 0.01 mol / L sodium hydrosulfite with the volume being 1 / 2 of that of the dilute nitric acid solution is dropwise added, stirring is conducted for 30 min at the room temperature, filtering is conducted, vacuum drying is conducted at the temperature of 70 DEG C, and the modified nano-silver-copper solder powder is obtained. The soldering flux comprises the following raw materials in parts by weight: 35-50 parts of esterified modified rosin, 10-15 parts of a self-made mixed activator, 1-2 parts of a surfactant, 3-5 parts of a thixotropic agent, 4-6 parts of a corrosion inhibitor, 2-3 parts of an antioxidant and 25-40 parts of an organic solvent. The prepared high-stability environment-friendly soldering paste has excellent chemical stability and corrosion resistance and has the potential of being widely applied and stored for a long time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to solder paste, and in particular to a nano solder paste and a preparation method thereof. Background Art

[0002] Solder paste is a new type of welding material that came into being with SMT. It is a paste-like mixture formed by mixing solder powder, flux and other surfactants, thixotropic agents, etc. It is mainly used for welding electronic components such as resistors, capacitors, and ICs on the surface of PCBs in the SMT industry. Solder paste is a complex system. It has a certain viscosity at room temperature and can initially stick electronic components to a predetermined position. At the welding temperature, as the solvent and some additives evaporate, the components to be welded are welded together with the printed circuit pads to form a permanent connection. At present, although the commercially available solder paste has good welding performance, it contains certain impurities. Not only will there be a certain amount of post-welding residue during the welding process, but it will also cause problems with the use and storage stability of the solder paste, and will also cause a certain degree of damage to the products that need to be welded. At the same time, the oxidizing metals in the solder paste not only affect its stability, but also have an adverse effect on the quality of welding. Summary of the invention

[0003] Purpose of the invention: The purpose of the present invention is to provide a nano solder paste; another purpose of the present invention is to provide a method for preparing the nano solder paste.

[0004] Technical solution: A nano solder paste, comprising the following components by weight: 80-90 parts of modified nano silver-copper solder powder, 9-19 parts of flux, and 0.1-0.5 parts of surface modified nano Ni particles; wherein: The preparation method of the modified nano silver-copper solder powder is as follows: adding the solder powder to a 0.01M dilute nitric acid solution with a volume 5 times its weight, stirring for 5 minutes, adding dropwise a mixture aqueous solution containing 0.02mol / L sodium hydroxide and 0.01mol / L sodium dithionite with a volume of 1 / 2 of the dilute nitric acid solution, stirring at room temperature for 30 minutes, filtering, and vacuum drying at 70°C to obtain the modified nano silver-copper solder powder; The soldering flux comprises the following raw materials in parts by weight: 35-50 parts of esterified modified rosin, 10-15 parts of homemade mixed activator, 1-2 parts of surfactant, 3-5 parts of thixotropic agent, 4-6 parts of corrosion inhibitor, 2-3 parts of antioxidant and 25-40 parts of organic solvent; The surface modified nano Ni particles are prepared by adding the nano Ni into a water solution with a volume 5 times the weight of the nano Ni, adding sodium silicate with a volume 1 / 5 of the weight of the nano Ni, stirring for 10 minutes, filtering, and drying at 60° C. in vacuum.

[0005] Preferably, the preparation method of esterified modified rosin is as follows: the rosin is crushed and added to ethanol with a volume 5 times the weight of the rosin, heated to 50°C to completely dissolve it, 18-crown-6 with a mass of 0.01 times the weight of the rosin is added, stirred for 5 minutes, concentrated sulfuric acid with a volume of 3% of ethanol is added, heated under reflux for reaction for 4 hours, cooled to 35°C, the reaction system is flushed into water with a volume 5 times the volume of ethanol under stirring, filtered, and dried at 50°C with air blowing.

[0006] Preferably, the homemade mixed activator is a mixture of L-malic acid and dihydrated malic acid copper complex, the mass ratio of the mixture of L-malic acid and dihydrated malic acid copper complex is 1:2, and after mixing, the mixture is crushed by a pulverizer and sieved through a 500-mesh sieve; The preparation method of the dihydrate malate copper complex is as follows: add malic acid to a 1.5M sodium hydroxide aqueous solution with an equal molar number as that of malic acid, stir and dissolve, add copper nitrate in an amount of 0.65 times the weight of L-malic acid, heat with stirring and reflux to react for 2 hours, evaporate under reduced pressure until some solid precipitates, cool by 5°C for crystallization for 4 hours, filter, and dry at 50°C with air blowing to constant weight.

[0007] Preferably, the surfactant is any one of OP-9 and OP-10.

[0008] Preferably, the thixotropic agent is any one of hydrogenated castor oil and modified hydrogenated castor oil.

[0009] Preferably, the corrosion inhibitor is benzotriazole.

[0010] Preferably, the antioxidant is any one of hydroquinone and catechol.

[0011] Preferably, the organic solvent is a mixture of tetrahydrofurfuryl alcohol, polypropylene glycol and tripropylene glycol methyl ether, and the mass ratio thereof is tetrahydrofurfuryl alcohol:polypropylene glycol:tripropylene glycol methyl ether=8:1:1.

[0012] Preferably, the solder powder is 96.5Sn3.0Ag0.5Cu.

[0013] A method for preparing nano solder paste comprises the following steps: S1. Add organic solvent and esterified modified rosin into a reaction vessel, heat to 110-140°C, stir until completely dissolved, add thixotropic agent, and stir until completely dissolved; S2, lowering the temperature of the reaction system to 60-80°C, adding the remaining raw materials required for preparing the flux, stirring and mixing, freezing at 0-4°C for 32-48h, and grinding to obtain the flux; S3, mixing the flux with the modified nano silver-copper solder powder and the surface modified nano particles, and stirring for 60 minutes to obtain a product. Beneficial Effects

[0014] 1. Use modified nano silver-copper solder powder to convert the originally oxidized silver and copper in the solder powder into nano silver and copper, making the temperature distribution more uniform during the brazing reaction, which can better promote the thermal motion of Sn and Cu atoms, and then promote the reaction and combination of Sn and Cu atoms, so that the interface IMC growth is more continuous and uniform.

[0015] 2. Adding surface-modified nano-Ni particles can cause aggregation on the surface of molten tin-silver-copper solder, reduce its surface tension and improve its spreadability.

[0016] 3. Adding esterified modified rosin and 18-crown-6 can remove the influence of some metal impurity ions, remove some inorganic salts, lower their melting point, make the solder joint expansion rate good, and leave less residue after welding.

[0017] 4. Add homemade mixed activator to make it more active, the solder joints are regular and full, and the residue after welding is small. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 It is a schematic diagram of the modification mechanism of the modified nano silver-copper solder powder of the present invention.

[0019] Figure 2 It is a schematic diagram of the esterification modified rosin reaction of the present invention. DETAILED DESCRIPTION

[0020] In order to make the technical solution of the present invention clearer, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments. Embodiment 1

[0021] Preparation of modified nano silver-copper solder powder: The solder powder was added to a 0.01M dilute nitric acid solution with a volume 5 times its weight, stirred for 5 minutes, and a mixture aqueous solution containing 0.02 mol / L sodium hydroxide and 0.01 mol / L sodium dithionite and 1 / 2 volume of the dilute nitric acid solution was added dropwise, stirred at room temperature for 30 minutes, filtered, and dried at 70°C in vacuum to obtain modified nano silver-copper solder powder, wherein the solder powder was selected from 96.5Sn3.0Ag0.5Cu.

[0022] Preparation of esterified modified rosin: Grind the rosin and add it to 5 times the volume of ethanol by weight of the rosin, heat it to 50°C to make it completely dissolved, then add 0.01 times the weight of rosin by weight of 18-crown-6, stir for 5 minutes, add 3% concentrated sulfuric acid by volume of ethanol, heat and reflux for 4 hours, cool to 35°C, flush the reaction system into 5 times the volume of ethanol by water while stirring, filter, and dry at 50°C with air blowing. Preparation of homemade mixed activator: The mixture of L-malic acid and dihydrate malic acid copper complex is mixed in a mass ratio of 1:2, and the mixture is crushed by a crusher and passed through a 500-mesh sieve to obtain a product; The preparation of dihydrated malic acid copper complex: Take malic acid and add it to a 1.5M sodium hydroxide aqueous solution with an equal molar number as malic acid, stir and dissolve, add copper nitrate in an amount of 0.65 times the weight of L-malic acid, heat with stirring and reflux to react for 2 hours, evaporate under reduced pressure until some solid precipitates, cool to 5°C for crystallization for 4 hours, filter, and dry at 50°C with air blowing to constant weight. Add peat to 5 times the volume of 5M dilute nitric acid aqueous solution, ultrasonicate at 40KHz for 1 hour, filter, adjust the filtrate to pH 8-9 with sodium carbonate while stirring, filter out insoluble matter, and concentrate under reduced pressure at 70°C to 1 / 5 of the volume of the filtrate, add 0.1 times the weight of the peat weight of 18-crown ether-6 while stirring, and dissolve to obtain.

[0023] Preparation of surface modified Ni nanoparticles: Add nano-Ni into an aqueous solution with a volume 5 times the weight of nano-Ni, add sodium metasilicate with a volume 1 / 5 of the weight of nano-Ni, stir for 10 minutes, filter, and dry at 60°C in vacuum to obtain the product.

[0024] Preparation of a nano solder paste: (1) Add 14.06 g of mixed organic solvent (tetrahydrofurfuryl alcohol: polypropylene glycol: tripropylene glycol methyl ether = 8:1:1) and 19.69 g of esterified modified rosin into a reaction vessel, heat to 110°C, stir until completely dissolved, add 1.69 g of hydrogenated castor oil, and stir until completely dissolved; (2) The temperature of the reaction system was lowered to 60°C, and 5.63 g of a homemade mixed activator, 0.56 g of an OP-9 surfactant, 2.25 g of benzotriazole, and 1.13 g of catechol were added, stirred and mixed, and the mixture was frozen at 0°C for 32 h, and ground to obtain a solder flux; (3) The flux was mixed with 400 g of modified nano silver-copper solder powder and 0.5 g of surface modified nano Ni particles and stirred for 60 min. Embodiment 2

[0025] Preparation of modified nano silver-copper solder powder: The solder powder was added to a 0.01M dilute nitric acid solution with a volume 5 times its weight, stirred for 5 minutes, and a mixture aqueous solution containing 0.02 mol / L sodium hydroxide and 0.01 mol / L sodium dithionite and 1 / 2 volume of the dilute nitric acid solution was added dropwise, stirred at room temperature for 30 minutes, filtered, and dried at 70°C in vacuum to obtain modified nano silver-copper solder powder, wherein the solder powder was selected from 96.5Sn3.0Ag0.5Cu.

[0026] Preparation of esterified modified rosin: Grind the rosin and add it to 5 times the volume of ethanol by weight of the rosin, heat it to 50°C to make it completely dissolved, then add 0.01 times the weight of rosin by weight of 18-crown-6, stir for 5 minutes, add 3% concentrated sulfuric acid by volume of ethanol, heat and reflux for 4 hours, cool to 35°C, flush the reaction system into 5 times the volume of ethanol by water while stirring, filter, and dry at 50°C with air blowing. Preparation of homemade mixed activator: The mixture of L-malic acid and dihydrate malic acid copper complex is mixed in a mass ratio of 1:2, and the mixture is crushed by a crusher and passed through a 500-mesh sieve to obtain a product; The preparation of dihydrated malic acid copper complex: Take malic acid and add it to a 1.5M sodium hydroxide aqueous solution with an equal molar number as malic acid, stir and dissolve, add copper nitrate in an amount of 0.65 times the weight of L-malic acid, heat with stirring and reflux to react for 2 hours, evaporate under reduced pressure until some solid precipitates, cool to 5°C for crystallization for 4 hours, filter, and dry at 50°C with air blowing to constant weight. Add peat to 5 times the volume of 5M dilute nitric acid aqueous solution, ultrasonicate at 40KHz for 1 hour, filter, adjust the filtrate to pH 8-9 with sodium carbonate while stirring, filter out insoluble matter, and concentrate under reduced pressure at 70°C to 1 / 5 of the volume of the filtrate, add 0.1 times the weight of the peat weight of 18-crown ether-6 while stirring, and dissolve to obtain.

[0027] Preparation of surface modified Ni nanoparticles: Add nano-Ni into an aqueous solution with a volume 5 times the weight of nano-Ni, add sodium metasilicate with a volume 1 / 5 of the weight of nano-Ni, stir for 10 minutes, filter, and dry at 60°C in vacuum to obtain the product.

[0028] Preparation of a nano solder paste: (1) Add 23.57 g of mixed organic solvent (tetrahydrofurfuryl alcohol: polypropylene glycol: tripropylene glycol methyl ether = 8:1:1) and 32.86 g of esterified modified rosin into a reaction vessel, heat to 130°C, stir until completely dissolved, add 2.86 g of hydrogenated castor oil, and stir until completely dissolved; (2) The temperature of the reaction system was lowered to 70°C, and 9.29 g of a homemade mixed activator, 1.07 g of an OP-10 surfactant, 3.57 g of benzotriazole, and 1.79 g of hydroquinone were added, stirred and mixed, and the mixture was frozen at 2°C for 40 h, and ground to obtain a solder flux; (3) The flux was mixed with 425 g of modified nano silver-copper solder powder and 1.5 g of surface modified nano Ni particles and stirred for 60 min. Embodiment 3

[0029] Preparation of modified nano silver-copper solder powder: The solder powder was added to a 0.01M dilute nitric acid solution with a volume 5 times its weight, stirred for 5 minutes, and a mixture aqueous solution containing 0.02 mol / L sodium hydroxide and 0.01 mol / L sodium dithionite and 1 / 2 volume of the dilute nitric acid solution was added dropwise, stirred at room temperature for 30 minutes, filtered, and dried at 70°C in vacuum to obtain modified nano silver-copper solder powder, wherein the solder powder was selected from 96.5Sn3.0Ag0.5Cu.

[0030] Preparation of esterified modified rosin: Grind the rosin and add it to 5 times the volume of ethanol by weight of the rosin, heat it to 50°C to make it completely dissolved, then add 0.01 times the weight of rosin by weight of 18-crown-6, stir for 5 minutes, add 3% concentrated sulfuric acid by volume of ethanol, heat and reflux for 4 hours, cool to 35°C, flush the reaction system into 5 times the volume of ethanol by water while stirring, filter, and dry at 50°C with air blowing. Preparation of homemade mixed activator: The mixture of L-malic acid and dihydrate malic acid copper complex is mixed in a mass ratio of 1:2, and the mixture is crushed by a crusher and passed through a 500-mesh sieve to obtain a product; The preparation of dihydrated malic acid copper complex: Take malic acid and add it to a 1.5M sodium hydroxide aqueous solution with an equal molar number as malic acid, stir and dissolve, add copper nitrate in an amount of 0.65 times the weight of L-malic acid, heat with stirring and reflux to react for 2 hours, evaporate under reduced pressure until some solid precipitates, cool to 5°C for crystallization for 4 hours, filter, and dry at 50°C with air blowing to constant weight. Add peat to 5 times the volume of 5M dilute nitric acid aqueous solution, ultrasonicate at 40KHz for 1 hour, filter, adjust the filtrate to pH 8-9 with sodium carbonate while stirring, filter out insoluble matter, and concentrate under reduced pressure at 70°C to 1 / 5 of the volume of the filtrate, add 0.1 times the weight of the peat weight of 18-crown ether-6 while stirring, and dissolve to obtain.

[0031] Preparation of surface modified Ni nanoparticles: Add nano-Ni into an aqueous solution with a volume 5 times the weight of nano-Ni, add sodium metasilicate with a volume 1 / 5 of the weight of nano-Ni, stir for 10 minutes, filter, and dry at 60°C in vacuum to obtain the product.

[0032] Preparation of a nano solder paste: (1) Add 31.40 g of mixed organic solvent (tetrahydrofurfuryl alcohol: polypropylene glycol: tripropylene glycol methyl ether = 8:1:1) and 39.26 g of esterified modified rosin into a reaction vessel, heat to 140°C, stir until completely dissolved, add 3.93 g of modified hydrogenated castor oil, and stir until completely dissolved; (2) The temperature of the reaction system was lowered to 80°C, and 11.78 g of a homemade mixed activator, 1.57 g of an OP-9 surfactant, 4.71 g of benzotriazole, and 2.36 g of catechol were added, stirred and mixed, and the mixture was frozen at 4°C for 48 h, and ground to obtain a solder flux; (3) The flux was mixed with 450 g of modified nano silver-copper solder powder and 2.5 g of surface modified nano Ni particles and stirred for 60 min. Comparative Example 1

[0033] The same as the first embodiment, except that the solder powder is not nano-modified. Comparative Example 2

[0034] Same as Example 1, except that surface modified nano Ni particles are not added. Comparative Example 3

[0035] Same as Example 1, except that the activator is only L-malic acid. Comparative Example 4

[0036] Same as Example 1, except that the esterified modified rosin is replaced by rosin.

[0037] The solder paste is printed on the treated copper sheet through a template, and its expansion rate is measured by melting under the same conditions. Five points are placed on each sample and the average value is taken. The expansion rate calculation formula is: Expansion rate (%) = (Dh) / D×100%, where D is the equivalent diameter of the solder paste and h is the height of the solder joint. The solder paste is printed on the treated copper sheet through a template. The electronic balance analyzes the weight change of the solder joint before and after simulated reflow soldering, and calculates the impurity residue of the flux in the solder paste. The solder paste is printed on the treated copper sheet through a template. The diameter of the printed board hole is 8mm, the thickness is 0.3mm, and the area is 50.27mm 2 Each sample was printed 5 times, and the test piece was placed horizontally on the surface of a molten solder bath at 250°C for 30 seconds, and then cooled at room temperature to calculate the average spreading area of ​​the solder joint. The cross-section of the solder joint obtained by the solder paste was sampled, and the thickness at different positions was measured by scanning electron microscopy. The average thickness of the interface IMC was obtained by taking the average value. The copper sheet was treated as follows: first, it was immersed in a 5% sodium hydroxide solution for 20 seconds, then immersed in 5mol / L hydrochloric acid for 15 seconds, and then washed with anhydrous ethanol and dried with argon gas.

[0038] The nano solder paste obtained in Examples 1 to 3 and Comparative Examples 1 to 4 was tested, and the test results are shown in Table 1.

[0039] Table 1 Test results of nano solder paste of examples and comparative examples From the results in Table 1, it can be seen that the nano solder paste prepared by the present invention cooperates with each other through the components. By adding modified nano silver-copper solder powder, the interface IMC growth can be made more continuous and uniform, and the average thickness of the interface IMC is better; by adding surface-modified nano Ni particles, its spreadability can be improved; by adding esterified modified rosin, the solder joint expansion rate can be good and the post-welding residue is small; by adding a homemade mixed activator, the solder joint is regular and full, and the post-welding residue is small.

[0040] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A nano solder paste, characterized in that: The composition comprises the following components by weight: 80-90 parts of modified nano silver-copper solder powder, 9-19 parts of flux, and 0.1-0.5 parts of surface modified nano Ni particles; wherein: The preparation method of the modified nano silver-copper solder powder is as follows: adding the solder powder to a 0.01M dilute nitric acid solution with a volume 5 times its weight, stirring for 5 minutes, adding dropwise a mixture aqueous solution containing 0.02mol / L sodium hydroxide and 0.01mol / L sodium dithionite with a volume of 1 / 2 of the dilute nitric acid solution, stirring at room temperature for 30 minutes, filtering, and vacuum drying at 70°C to obtain the modified nano silver-copper solder powder; The soldering flux comprises the following raw materials in parts by weight: 35-50 parts of esterified modified rosin, 10-15 parts of homemade mixed activator, 1-2 parts of surfactant, 3-5 parts of thixotropic agent, 4-6 parts of corrosion inhibitor, 2-3 parts of antioxidant and 25-40 parts of organic solvent; The surface modified nano Ni particles are prepared by adding the nano Ni into a water solution with a volume 5 times the weight of the nano Ni, adding sodium silicate with a volume 1 / 5 of the weight of the nano Ni, stirring for 10 minutes, filtering, and drying at 60° C. in vacuum.

2. The nano solder paste according to claim 1, characterized in that: The preparation method of esterified modified rosin is as follows: the rosin is crushed and added to ethanol with a volume 5 times the weight of the rosin, heated to 50°C to make it completely dissolved, 18-crown-6 with a mass 0.01 times the weight of the rosin is added, stirred for 5 minutes, concentrated sulfuric acid with a volume of 3% of ethanol is added, heated under reflux for reaction for 4 hours, cooled to 35°C, the reaction system is poured into water with a volume 5 times the volume of ethanol under stirring, filtered, and dried at 50°C with air blowing.

3. The nano solder paste according to claim 1, characterized in that: The homemade mixed activator is a mixture of L-malic acid and dihydrated malic acid copper complex, the mass ratio of the mixture of L-malic acid and dihydrated malic acid copper complex is 1:2, and after mixing, it is crushed by a pulverizer and passed through a 500-mesh sieve; The preparation method of the dihydrate malate copper complex is as follows: add malic acid to a 1.5M sodium hydroxide aqueous solution with an equal molar number as that of malic acid, stir and dissolve, add copper nitrate in an amount of 0.65 times the weight of L-malic acid, heat with stirring and reflux to react for 2 hours, evaporate under reduced pressure until some solid precipitates, cool by 5°C for crystallization for 4 hours, filter, and dry at 50°C with air blowing to constant weight.

4. The nano solder paste according to claim 1, characterized in that: The surfactant is either OP-9 or OP-10.

5. The nano solder paste according to claim 1, characterized in that: The thixotropic agent is any one of hydrogenated castor oil and modified hydrogenated castor oil.

6. The nano solder paste according to claim 1, characterized in that: The corrosion inhibitor is benzotriazole.

7. The nano solder paste according to claim 1, characterized in that: The antioxidant is any one of hydroquinone and catechol.

8. The nano solder paste according to claim 1, characterized in that: The organic solvent is a mixture of tetrahydrofurfuryl alcohol, polypropylene glycol and tripropylene glycol methyl ether, and the mass ratio thereof is tetrahydrofurfuryl alcohol:polypropylene glycol:tripropylene glycol methyl ether=8:1:

1.

9. The nano solder paste according to claim 1, characterized in that: The solder powder used is 96.5Sn3.0Ag0.5Cu.

10. A method for preparing a nano solder paste according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. Add organic solvent and esterified modified rosin into a reaction vessel, heat to 110-140°C, stir until completely dissolved, add thixotropic agent, and stir until completely dissolved; S2, lowering the temperature of the reaction system to 60-80°C, adding the remaining raw materials required for preparing the flux, stirring and mixing, freezing at 0-4°C for 32-48h, and grinding to obtain the flux; S3, mixing the flux with the modified nano silver-copper solder powder and the surface modified nano Ni particles, and stirring for 60 minutes to obtain a product.